Short-term responses of phytoplankton size-fractionated structure and photosynthetic physiology to thermal effluent in a subtropical coastal bay - Hu, Simin; Zhang, Chen; Liu, Qingxia; Li, Tao; Huang, Hui; Liu, Sheng (Frontiers in Marine Science, 2023)
Elevated water temperature caused by the thermal discharge from power plants can exert multiple ecological impacts on the phytoplankton community in coastal ecosystems. Most recent studies have focused on the reshaping effects on the community structure; however, the short-term response of phytoplankton physiology to thermal discharge remains unclear. This study conducted research on the scope of thermal discharge from the nuclear power plant and the size-fractionated phytoplankton structure combined with photosynthetic physiology in Daya Bay, China. The thermal discharge significantly affected the surface temperature in the outlet regions, and the thermal plume mainly diffused along the northeast coast of the outfall site, resulting in a significant difference in the surface temperature between the inlet and outlet transects (p<0.05). Elevated surface temperatures decreased the total chlorophyll a concentrations by 33.19% at the outlet regions, with pico-phytoplankton decreasing the most. Chlorophyll a concentrations were higher at sites further away from the outlets, indicating that elevated water temperature might stimulate the rapid growth of phytoplankton, especially nano-phytoplankton which replaced pico-phytoplankton as the dominant group at stations away from the outlets. Significant negative correlations were observed between the photochemical quantum yield (Fv/Fm) and temperature (p<0.05), and the relative electron transport rate (rETR) and temperature (p<0.05). Phytoplankton showed a normal photosynthetic physiological state at most sites with a surface temperature<33°C but was severely affected at the outlet site with a 5°C rise, decreasing from ~0.5 on the inlet transect to 0.07. During the diurnal survey, the high temperatures near the outlet at midday had a compensatory effect on phytoplankton’s light suppression. The results indicated that the physiological state of phytoplankton was clearly influenced by the thermal discharge with diurnal variation, and different size-fractionated phytoplankton groups exhibited heterogeneous responses. The findings may provide further insights into the ecological impacts of thermal discharges as well as global warming in subtropical regions.